Views of Consumers, Farmers and Stakeholders on Alternative Dairy Cattle Housing Systems - Karmen Erjavec; Marija Klopčič (Animals, 2022)
Alternative housing systems for dairy cattle have recently emerged, such as compost-bedded packs and artificial floor ones. To determine their acceptability among categories of people with a connection to animal husbandry, this study aimed to identify and compare the acceptability of (alternative) housing systems and attitudes to aspects of housing systems for dairy cattle among Slovenian consumers, farmers, and stakeholders. Farmers (N = 306), consumers (N = 508), and stakeholders (N = 40) were interviewed about their views on the main aspects (animals, farmers, products, environment) of housing systems for dairy cattle, the acceptance of four housing systems, and important housing features. The results show that consumers, stakeholders, and conventional farmers preferred housing systems with an artificial floor, while organic farmers preferred a housing system with a compost-bedded pack. Consumers and organic farmers expressed the greatest acceptance of almost every aspect of the housing system, except for a sufficient income for farmers and a low workload. Conventional farmers and stakeholders hold similar views, except for the expectation that the animals have enough space to move around, the image of the landscape, and the animals’ health and wellbeing, where stakeholders showed more acceptance than conventional farmers. The results imply that systematically planned information aimed at different target categories is needed to increase the acceptance of (alternative) housing systems for cattle.